Islamic Republic of Iran : 2018 Article IV Consultation. - International Monetary Fund. Middle East and Central Asia Dept. (Washington, D.C. : International Monetary Fund, 2018)
This 2018 Article IV Consultation highlights that the real GDP growth of Iran is expected to reach 4.3 percent in 2017/18. In the first half of 2017/18, recovery broadened to the non-oil sector, aided by supportive fiscal and monetary policies and a recovery in construction and services activity. The unemployment rate declined to 11.7 percent in the first half of 2017/18, but remained particularly high for youth and women. Inflation averaged 9.9 percent during the first 11 months of 2017/18 aided by moderation in food prices and stable administered prices. Real GDP growth is expected to ease to 4 percent in 2018/19 and is forecast to average 4.5 percent over the medium-term.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet